THE EYE — MIRROR OF CARDIOVASCULAR DISORDER. RELATIONSHIP OF THE RETINA FUNCTIONAL STATE AND THE HYPERTENSION SEVERITY - V. S. Zadionchenko; T. V. Adasheva; A. M. Shamshinova; M. A. Arakelyan (Рациональная фармакотерапия в кардиологии, 2016)
Aim. To study the retina state by functional methods in patients with arterial hypertension (HT) of various degrees. Material and methods. Patients with uncomplicated HT of 1-3 degrees (n=81) and healthy subjects (n=20) of control group were examined. Routine (direct ophthalmoscopy) and functional (evaluation of contrast and color sensitivity of the retina, electroretinography) methods were used. Results. Functional retinal changes (reduction in color and contrast sensitivity) progressed with increasing HT degree. These changes were located in the area of central retinal artery (paramacular area) and area of choroidal blood flow (macular region). Retinal bioelectrical activity disturbance was also found by the electroretinography. Conclusion. The identified functional disorders suggest the retina involvement in the pathological process even in the early HT and may be associated with its severity. It confirms a relationship of HT with disorders of eye as a target organ in HT. Published data and results of our studies can refute the point of view about impossibility of changes assessment on the eye fundus in patients with uncomplicated HT, and indicates that it was premature exclusion of the eye from the list of target organs in HT.